Assessment of Natural Radioactivity and Radon Exhalation in Peruvian Gold Mine Tailings to Produce a Geopolymer Cement - Liza, R.; Pereyra, P.; Rau, J.; Guzman, M.; Sajó-Bohus, L.; Palacios Fernandez, D. (MDPI, 2023)
Mining generates significant amounts of waste that can represent a source of contamination for areas close to the extraction area, generating a negative impact both on the environment and the health of people. This study aims to evaluate the radiological risk derived from exposure to natural radionuclides contained in tailings from Peruvian gold mines and to establish whether the tailings can be used as raw materials in building materials. The mine tailings come from a mining project in the northern highlands of Peru. Radon exhalation was measured using Rad7 in a closed chamber and activity concentration of ²²⁶Ra, ²³²Th, and ⁴⁰K radioisotopes by gamma spectrometry using NaI 3” x 3” detector. Maximum activity concentrations measured for ²²⁶Ra and ²³²Th were 15.38 Bq kg⁻¹ and 11.9 Bq kg⁻¹, respectively; meanwhile, activity concentration for ⁴⁰K ranged from 182.7 Bq kg⁻¹ to 770.8 Bq kg⁻¹. All activity concentrations were below the worldwide average except for ⁴⁰K. The radon exhalation rate varied from 2.8 to 7.2 mBq kg⁻¹ h⁻¹. The gamma index (Iy), and radiological parameters, including the Radium equivalent activity (Raeq), and the external hazard index (Hₑₓ), being below the recommended levels by UNSCEAR, ensure the safe use of these mines tailing to produce a geopolymer cement.
Keywords: Mine tailings; Radiological risk; Natural radionuclides; https://purl.org/pe-repo/ocde/ford#2.07.05